Error Analysis of Students’ Sentence Structure in Writing Application Letter - Rika Arista; Dewi Yana; Sri Sugiharti (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
This research was aimed to describe the kind of the classification and the dominant of error that made by the student in writing application letter at the twelfth grade of SMKN 5 Batam in the academic year 2015/2016. The analysis of error in the foreign language learning was important to help the teacher to take an immediate action to avoid the re-occurrence of error. This study was limited only in the classification of error in the element of sentence and the application letter format. The research was conducted in April 2016 and was held on twelfth grade with the number of sample was 50 students. Data was collected by the written test and analyzed by descriptive method to describe the students’ error. The result of the research presented there was 1188 errors in the application letter format and sentence structure in writing application letter. There were 45.03% with number 535 errors of omission, 14.06% with number 167 errors of addition, 36.03% with number 428 errors of selection, and 4.88% with number 58 errors of ordering. The dominant sentence structure error was 7.15% with number 85 errors of omission in the adverbial and adverbial complement element of the simple sentence. A lot of error in the element of the sentence structure in writing application letter caused by the omission, selection, and addition of some letter in the element. The error also caused by the application of the capital letter, punctuation, and conjunction while the error of ordering was due to the sequence of the element in the sentence structure was incorrect placed. Based on the finding of the research, the researcher suggested that the teacher should pay more attention in the writing subject learning and correct the error directly to avoid the re-occurrence of the error, while for the school should facilitate the overall English teaching. Keywords: error analysis and sentence structure